Избранное: [стихотворения, поэмы] / Борис Пастернак - Пастернак Борис Леонидович (ЭКСМО, 2003)
Экземпляры: ф.5 (2007) / Инвентарный номер: 51645 / Цена: / Сис.шифр: 84(2Рос=Pус)6-5 / Авт.знак: П 19 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Pус)6-5